Hubungan Nilai Indeks Massa Tubuh dengan Usia Menarche pada Remaja di SMPN Abulyatama Kecamatan Kuta Baro Kabupaten Aceh Besar Provinsi Aceh - Lia Wandari; Yasrida Nadeak; Rosmani Sinaga (Pusat Riset dan Inovasi Nasional, 2025)
Background: Menstruation is the result of a complex interaction that involves the hormonal system and body organs, namely the hypothalamus, pituitary, ovaries and uterus. Things that affect the age of menarche are nutritional status, diet, family economic status, and sports activities.BMI is determined by body weight and height. The impact if young women experience early menarche, which is less than 12 years old, is at risk of developing breast cancer and ovarian cancer To find out the relationship between body mass index values ​​and the age of menarche in young women at Abulyatama Middle School, Aceh Besar district in 2023. This research method is analytic with a cross sectional study design. Using Independent Variables and dependent variables. Sampling technique Random sampling.Data analysis using Chi Square. Results The showed that out of 30 respondents whose body mass index was underweight, 13 respondents (43.3%) had overweight nutritional status, 10 respondents (33.3%) and normal nutritional status, 7 respondents (23.3%). Conclusion: the relationship between body mass index values ​​and menarche age in young women at Abulyatama Junior High School, Aceh Besar District. Based on the test results using Chi Square, it is known that P Value = 0.013, then Ho is rejected, Ha is accepted.